2013
DOI: 10.1007/s00394-013-0508-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chromium on inflammatory markers, 1st and 2nd phase insulin secretion in type 2 diabetes

Abstract: In conclusion, other than the improvement of SI, GaCr could also improve the second phase of insulin responsivity (Φs) and IL-6. However, δ-IL-6 was correlated with neither δ-SI nor δ-Φs which indicated that the improvement of SI and Φs might involve mechanisms other than lower inflammatory effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Next, 172 titles and the abstracts were screened; of these, 47 publications were considered relevant and the full‐text articles were obtained. After careful assessment, a total of 28 RCTs that met our inclusion criteria were included in the present pooled analysis . Reasons for rejecting the other eight articles were listed in Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, 172 titles and the abstracts were screened; of these, 47 publications were considered relevant and the full‐text articles were obtained. After careful assessment, a total of 28 RCTs that met our inclusion criteria were included in the present pooled analysis . Reasons for rejecting the other eight articles were listed in Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty RCTs (22 study arms) of patients with T2DM, including all in the existing meta-analyses and the one additional RCT 24 that had been completed after the last metaanalysis, are summarized in this report. A few studies controlled for or monitored background diets and physical activity levels, though most did not.…”
Section: Synthesizing the Results Of The Data Setmentioning
confidence: 99%
“…Abbreviations: Cr, chromium; IGT, impaired glucose tolerance; RCTs, randomized controlled trials. 22 Cefalu et al (2010) 23 Chen et al (2014) 24 Crawford et al (1999) 25 Evans (1989) 26 Ghosh et al (2002) 27 Gunton et al (2005) 28 Grant and McMullen. (1982) 29 Grant et al (1997) 30 Hermann et al (1998) 31 Hermann et al (1994) 32 Jain et al (2012) 40 Lee and Reasner (1994) 41 Li et al (1992) 42 Li (1994) 43 45 Martinez et al (1985) 46 Mossop (1983) 47 Offenbacher and Pi-Sunyer (1980) 48 Offenbacher et al (1985) 49 Pasman et al (1997) 50 Pei et al (2006) 51 Rabinovitz et al (1983) 52 Rabinovitz et al (2004) 53 Racek et al (2006) 54 Riales et al (1981) 55 Singer and Geohas (2006) 56 Sharma et al (2011) 57 Sherman et al (1968) 58 Thomas and Gropper (1996) 59 Urberg and Zemel (1987) …”
Section: Studies Measuring Hba1cmentioning
confidence: 99%
“…Changes in BMI were reported in eight trials and 19 trials reported changes in body weight . The reported mean BMI of all included trials was over 25 kg/m 2 , therefore all included participants were considered as subjects with overweight/obesity.…”
Section: Resultsmentioning
confidence: 99%
“…The reported mean BMI of all included trials was over 25 kg/m 2 , therefore all included participants were considered as subjects with overweight/obesity. Of the 21 RCTs, 12 reported body fat percentage, eight RCTs measured waist circumference and only three studies specified the waist to hip ratio . In terms of study quality, 13 trials were categorized as high‐quality with Jadad score of ≥3; and eight as low‐quality studies with Jadad score of <3 (Table ).…”
Section: Resultsmentioning
confidence: 99%